Licochalcone A Protects the Blood–Milk Barrier Integrity and Relieves the Inflammatory Response in LPS-Induced Mastitis - Guo, Wenjin; Liu, Bingrun; Yin, Yunhou; Kan, Xingchi; Gong, Qian; Li, Yanwei; Cao, Yu; Wang, Jianfa; Xu, Dianwen; Ma, He; Fu, Shoupeng; Liu, Juxiong (Frontiers in Immunology, 2019)
Background/aims: Mastitis is an acute clinical inflammatory response. The occurrence and development of mastitis seriously disturb women's physical and mental health. Licochalcone A, a phenolic compound in Glycyrrhiza uralensis, has anti-inflammatory properties. Here, we examined the effect of licochalcone A on blood-milk barrier and inflammatory response in LPS-induced mice mastitis. Methods: In vivo, we firstly established mice models of mastitis by canal injection of LPS to mammary gland, and then detected the effect of licochalcone A on pathological indexes, inflammatory responses and blood-milk barrier in this model. In vivo, Mouse mammary epithelial cells (mMECs) were treated with licochalcone A prior to the incubation of LPS, and then the inflammatory responses, tight junction which is the basic structure of blood-milk barrier were analyzed. Last, we elucidated the anti-inflammatory mechanism by examining the activation of mitogen-activated protein kinase (MAPK) and AKT/NF-κB signaling pathways in vivo and in vitro. Result: The In vivo results showed that licochalcone A significantly decreased the histopathological impairment and the inflammatory responses, and improved integrity of blood-milk barrier. The In vitro results demonstrated that licochalcone A inhibited LPS-induced inflammatory responses and increase the protein levels of ZO-1, occludin, and claudin3 in mMECs. The in vivo and in vitro mechanistic study found that the anti-inflammatory effect of licochalcone A in LPS-induced mice mastitis was mediated by MAPK and AKT/NF-κB signaling pathways. Conclusions & Implications: Our experiments collectively indicate that licochalcone A protected against LPS-induced mice mastitis via improving the blood–milk barrier integrity and inhibits the inflammatory response by MAPK and AKT/NF-κB signaling pathways.